"A censura de dialetos" na colônia Erechim: a aplicação da Lei de Nacionalização (1937-1945) - Enich, Cristiano Alexandre (2014)
The changes in Brazil between 1937 - 1945 amounted to various sectors of the country, including language / dialects of communication between foreign, mainly immigrants from Italian and German origin. The objective of this study is to analyze how the repression occurred in the nationalization process and how it was applied to "Censorship Dialects" Erechim the colony during theNew State. After analyzing the sources, becoming basically the use of interviews and cataloged by the Municipal Historical Archive Miguel Juarez Illa Font Erechim, became clear that these immigrants have not lost as printed interviews and transitions became evident that these immigrants do not lose their identity, but with the forced change communication and the obligation to adopt the portuguese language in their daily lives at the expense of the mother tongue, experienced authoritarianism and violence of Silence Law, this is, nationalization decreed by President Getúlio Vargas.